PENGARUH APLIKASI GEOGEBRA TERHADAP HASIL BELAJAR MAHASISWA PADA MATERI GEOMETRI TRANSFORMASI - Wiwin Apriani; Rahmi Hayati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
This study aims to determine whether there are differences in the learning outcomes of mathematics education students at a university in Aceh who are taught using geogebra applications with students who are taught using conventional learning methods in the transformation geometry course. This research uses a quantitative approach with a true experimental type of research. The population in this study were all students of mathematics education at Almuslim University. While the samples used were students who took the Transformation Geometry course. The sample used in this study amounted to 60 people. Furthermore, the students were divided into 2 classes, namely 20 people into the experimental class and 20 people into the control class. In the experimental class, learning uses the geogebra application and in the control class using conventional learning. The results obtained show the difference in the average learning outcomes in the two classes. The difference in learning outcomes of the two classes can be seen by using the t-test independent sample test. These results indicate that the value of Sig. (2 Tailed) < 5 % . As for the value of Sig. (2 Tailed) of 0.000. This means that H0 is rejected. Thus, it can be concluded that the average student learning outcomes on the transformation geometry material in the control class are included in the less criteria. While the average student learning outcomes on the material of transformation geometry using the geogebra application are included in good criteria.